Analysis of the Powertrain Component Size of Electrified Vehicles Commercially Available on the Market - Sanjarbek, Ruzimov; Mavlonov, Jamshid; Mukhitdinov, Akmal (Communications - Scientific Letters of the University of Zilina, 2022)
The paper aims to present an analysis of the component sizes of commercially available vehicles with electrified powertrains. The paper provides insight into how the powertrain components (an internal combustion engine, an electric motor and a battery) of mass production electrified vehicles are sized. The data of wide range of mass production electrified vehicles are collected and analyzed. Firstly, the main requirements to performance of a vehicle are described. The power values to meet the main performance requirements are calculated and compared to the real vehicle data. Based on the calculated values of the power requirements the minimum sizes of the powertrain components are derived. The paper highlights how the sizing methodologies, described in the research literature, are implemented in sizing the powertrain of the commercially available electrified vehicles.
Keywords: electrified powertrain; hybrid electric vehicle; battery electric vehicle; component sizing; power requirement; drive cycle